2019
DOI: 10.3390/w11122528
|View full text |Cite
|
Sign up to set email alerts
|

A New Technical Concept for Water Management and Possible Uses in Future Water Systems

Abstract: A new degree of freedom in water management is presented here. This is obtained by displacing water, and in this paper is conceptually explained by two methods: using an excavated cavern as a container for compressed air to displace water, and using inflatable balloons. The concepts might have a large impact on a variety of water management applications, ranging from mitigating discharge fluctuation in rivers to flood control, energy storage applications and disease-reduction measures. Currently at a low techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The capacity of the reservoir has to be adapted to the ramping rate of the power plant, and space constraints can be an issue particularly when dampening reservoirs are retrofitted to existing power plants. An alternative solution using water storage for dampening the effect of hydropeaking has been proposed by Storli and Lundström (2019) who presented the Air Cushion Underground Cavern (ACUR), providing underground storage where compressed air is used to control the storage and release of water. This solution would be suited to underground power plants and is potentially easier to retrofit at existing power plants since no structure is required to be built at the power plant outlet.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of the reservoir has to be adapted to the ramping rate of the power plant, and space constraints can be an issue particularly when dampening reservoirs are retrofitted to existing power plants. An alternative solution using water storage for dampening the effect of hydropeaking has been proposed by Storli and Lundström (2019) who presented the Air Cushion Underground Cavern (ACUR), providing underground storage where compressed air is used to control the storage and release of water. This solution would be suited to underground power plants and is potentially easier to retrofit at existing power plants since no structure is required to be built at the power plant outlet.…”
Section: Introductionmentioning
confidence: 99%
“…One approach that has been suggested is to divert some of the discharge during hydropeaking before the tailrace and to gradually introduce it to the main river downstream [18]. It has also been suggested that discharge water can be temporarily stored in an Air Cushion Underground Reservoir (ACUR) and gradually released into the tailrace in times of no hydropeaking [9,19]. An additional approach could be to use the inherent inertia in the river to reduce the impact of hydropeaking in some stretches of a river.…”
Section: Introductionmentioning
confidence: 99%
“…Given that mortality is dependent on the hydropeaking flow regime, a range of recommendations have been made to mitigate effects including modifying operational regimes (Moreira et al, 2019) and installation of hydraulic structures such as buffer reservoirs and retention basins (Reindl et al, 2022). Additionally, mitigation technologies including the Air Cushion Underground Reservoir (ACUR) (Storli, 2017;Storli & Lundström, 2019) that uses compressed air to dampen changes in downstream flow conditions during hydropeaking have recently been investigated. Fish behaviour also affects stranding mortality.…”
Section: Introductionmentioning
confidence: 99%